Effect of Ethnic Diversity on Employee Performance at the National Museum of Kenya - Nguta, Lydia; Omuya, Jacqueline (Rescollacom (Research Collaborations Community), 2024)
According to the assessment report from the Quality Assessment and Performance Improvement Strategy, it was identified that the staff members of the state corporations in Kenyan exhibited low performance levels, leading to a decline in employee satisfaction. The National Cohesion and Integration Commission (NCIC) audit report revealed disparities in race and ethnicity within the corporations. The primary objective of the research was to examine the impact of ethnic diversity on the performance of employees at the National Museum of Kenya. The research drew guidance from similarity/attraction theory. In the study, a descriptive cross-sectional survey design was employed. The total population comprised 550 employees at various personnel levels at the National Museum of Kenya headquarters. A population sample of 110 members was selected through Stratified random sampling. Data was collected using a semi-structured questionnaire administered to the chosen sample. To ensure the reliability of the instrument, Cronbach's Alpha was employed. Descriptive statistics was utilized for analysis of quantitative data, with the results presented through tables, figures, graphs, and prose. The research uncovered significant positive correlations between ethnic diversity and employee performance within the National Museum of Kenya. This underscores the importance of cultivating diversity when hiring personnel, as it contributes to enhanced performance. Furthermore, ensuring equal opportunities for promotion fosters employee motivation and dedication. To maximize the benefits of ethnic diversity, organizations should actively promote it and harness the collaborative potential of diverse work groups to improve both individual and organizational performance.